زمان له‌ پرۆسه‌ی شیعردا، شیعر له‌ ماڵی زمان‌دا شیعرییەتی زمان و بوون له‌ دیوانی "گه‌ڕانه‌وه‌ی زه‌رده‌شت"ی "ئه‌حمه‌دی مه‌لا"دا - ئیبراهیم, محه‌مه‌د نه‌بی; مەعروف, هەرێم عوسمان (Sulaimani Journal for Humanities, 2023)
Speaking about language and existence in poetry leads us to speak about what existence, language and poetry are, so, we have to discusses the three of them. Poetry speaks about the world and man, and takes us to the philosophical meanings of existence and language. Existence is the foundation of all beings, and man is the highest of all the beings. That is why we see them integrated into each other: Existence is the foundation of human being, and in human being, we find language among the rarest incidents, and with poetry it reaches the peak of its reality. In this research, we analyzed the meanings of existence, poetry and language, and then we searched in the collection of 'The Return of Zoroaster' by the poet Ahmadi Mulla, about the mergers and reflections of this issue. In the beginning, we analyzed the meanings of existence, language and poetry from the existential philosophy worldview, and then we showed these topics in the above-mentioned collection.
Keywords: existence; language; poetry; philosophy; the return of Zoroaster